CRYPTO CURRENCY ‒ A NEW PHENOMENON IN MONETARY CIRCULATION - B, Ilyasova G.; F, Bekmukhametova A.; Jam, Farooq Ahmed (Farabi Journal of Social Sciences, 2019)
The world of crypto currency is developing very quickly. For example, bitcoin over the past five years outperformed by its return investments such as gold, stocks and real estate. Also recently, hundreds of new crypto-currencies appeared on the market, which in their essence copy each other, differing by very insignificant characteristics. However, only a small part of them truly represents value and in the long run it can blow up the market, as bitcoin did in 2016-2017. Interest in the blockchain and crypto currency in Kazakhstan goes both “from above” and “from below”: while the government is taking a course to introduce a new promising technology, ordinary citizens view the ether and bitcoin as a good way of investing. The business community also shows a high interest in the topic, because the development of blockchain-technologies and the increasing role of the crypto currency are a good space for the formation of start-ups. The government of Kazakhstan for the first time clearly indicated its interest in the topic of blockchain in the summer of 2016: a workshop was held at the IX Astana Economic Forum on the prospects of blockchain in the state administration. During 2016-2017 years, In Kazakhstan, several major state-level block projects were announced. Today, the country is confidently moving towards the blockchain, and this movement aims to make Kazakhstan a technologically advanced country and increase its investment attractiveness. Bitcoin, according to the forecast, will continue to grow in price ‒ up to $ 5000 per unit. Therefore, in Kazakhstan, mining of bitcoins (mining) is becoming a popular business. This article reveals the essence, functions and prospects of the crypto currency as a new trend in the currency system of many countries.